Does donor-recipient body mass index ratio influence heart transplantation outcomes?? - Matiullah Masroor (BMC Cardiovascular Disorders, 2025)
Abstract Background Obesity is a common risk factor for heart failure, and heart transplantation (HTx) is the treatment of choice for end-stage heart failure. Due to the limited availability of the donor’s heart, efforts are made to increase the donor pool on one hand and to find predictors that can impact HTx outcomes on the other hand. These predictors can help improve donor organ allocation and HTx outcomes. This study aims to investigate the impact of the donor-recipient BMI ratio on follow-up mortality and other outcomes after HTx. Methods From 2012 to 2021, 821 patients underwent HTx in our centre. Patients under 18 years, re-transplantation, multiorgan transplantation, and missing recipient and donor BMI data were excluded. The final sample size of 653 patients was divided into three quartile categories based on the donor-recipient (D-R) BMI ratio. D-R BMI ratio < 0.86 (n = 156), D-R BMI ratio 0.86–1.12 (n = 338), and D-R BMI ratio > 1.12 (n = 159). Analysis of variance and chi-square test with post hoc test according to the types of variables were performed to find differences among the groups. Kaplan-Meier survival analysis was used to evaluate survival, and the difference between the curves was checked with the log-rank test. Cox regression analysis was used to adjust for confounders and find independent predictors of mortality. Results Some preoperative variables were statistically different between the groups. The D-R BMI ratio did not impact follow-up mortality after adjustment for confounders. The 7-year survival in D-R BMI ratios < 0.86, 0.86–1.12, and > 1.12 was 73%, 68%, and 70% respectively (p = 0.532). There was no significant difference in other postoperative outcomes, including ICU stay, systemic complications, and mechanical circulatory support use, between the groups based on unadjusted analysis. Conclusion The donor-recipient BMI ratio had no significant impact on post-transplantation mortality. Postoperative outcomes other than survival were also comparable between the groups. These outcomes were observed in a specific D-R BMI ratio range (0.77–1.26), and extreme BMI ratios may have different results. The results of this study support the liberal use of donor and recipient BMI during patient matching, which can decrease the likelihood of potential donor non-use and subsequently increase the donor pool.